2011
DOI: 10.1021/jf1041855
|View full text |Cite
|
Sign up to set email alerts
|

Particle-Stabilizing Effects of Flavonoids at the Oil−Water Interface

Abstract: It has been shown that some common food flavonoids can act as excellent stabilizers of oil-in-water emulsions through their adsorption as water-insoluble particles to the surface of the oil droplets, i.e., Pickering emulsions are formed. Flavonoids covering a wide range of octanol-water partition coefficients (P) were screened for emulsification behavior by low shear mixing of flavonoid+n-tetradecane in a vortex mixer. Most flavonoids with very high or very low P values were not good emulsifiers, although ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(95 citation statements)
references
References 42 publications
0
95
0
Order By: Relevance
“…(2012) by using glycol stearate:propylene glycol:liquid paraffin (3:6:1) [23] for enhancing the bioavailability of Luteolin which has poor water solubility. The ointment base increased the solubility of the tested material and were helped to get a homogeneous mixture with enhanced penetration capacity [24,25]. An appropriate amount of Luteolin (LUT) (Sigma Chemical Co. (USA)) was added in this mixture to prepare for 0.5 % and 1 % (w/w) Luteolin test ointments.…”
Section: Luteolin Ointment Processingmentioning
confidence: 99%
“…(2012) by using glycol stearate:propylene glycol:liquid paraffin (3:6:1) [23] for enhancing the bioavailability of Luteolin which has poor water solubility. The ointment base increased the solubility of the tested material and were helped to get a homogeneous mixture with enhanced penetration capacity [24,25]. An appropriate amount of Luteolin (LUT) (Sigma Chemical Co. (USA)) was added in this mixture to prepare for 0.5 % and 1 % (w/w) Luteolin test ointments.…”
Section: Luteolin Ointment Processingmentioning
confidence: 99%
“…Although a great many studies have been conducted on Pickering emulsions using traditional inorganic or synthetic particles, there is a relative paucity of literature on food-compatible particulate materials from natural edible sources, examples, include cellulose nanocrystals 22 , chitin nanocrystals 23 , modified starch 24 , soy protein nanoparticles 25 , flavonoid particles 26 , micellar casein coated nanoemulsion droplets 27 and whey protein microgels 28,29 . Soft solid particles such as whey protein microgels can be a particularly effective system to resist displacement by bile salts because soft solid particles deform during adsorption increasing the adsorption energies by orders of magnitude relative to rigid particles 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Tiliroside is a relatively hydrophobic compound, despite having a hydrophilic conjugating side chain (coumaroyl-glucoside), it has a Log P of 2.7 (Luo et al, 2011). It is therefore feasible that tiliroside can diffuse across biological membranes.…”
Section: Transport Studymentioning
confidence: 99%
“…Kaempferol is more hydrophobic (log P = 3.2 (Luo et al, 2011)) than tiliroside, with a lower molecular weight (286) and, thus would be expected to diffuse passively across biological membranes. We found that 5% of kaempferol aglycone was transferred from the apical to basolateral membrane, and that no significant difference in transfers were observed in both directions, at similar constant linear rates (see Figure 2 and 3b).…”
Section: Transport Studymentioning
confidence: 99%
See 1 more Smart Citation